Fatal systemic reactions, concurrent of anaphylaxis and systemic toxic reactions to hymenoptera-sting - Suryana, Ketut; Sindhughosa, Dwijo Anargha (International Journal of Advances in Medicine, 2022)
Hymenoptera-sting can cause localized and systemic reactions (SR). SRs such as anaphylaxis and systemic toxic reactions (STR). It is estimated to occur in 3% of adults and can be life-threatening. Diagnosis is based on clinical manifestations, previous of allergic history, IgE-mediated confirmation and the offending insect identification. Anaphylaxis patients should immediately receive adrenaline intramuscularly, emergency medical attention and other supporting treatment. We report a 36-year-old man with fatal SRs, concurrent of anaphylaxis and systemic toxic reaction due to multiple hymenoptera-stings.